Organic matter interactions with natural manganese oxide and synthetic birnessite - Allard, Sebastien; Gutierrez, L.; Fontaine, C.; Croué, J.; Gallard, H. (Elsevier, 2017)
© 2017 Elsevier B.V.Redox reactions of inorganic and organic contaminants on manganese oxides have been widely studied. However, these reactions are strongly affected by the presence of natural organic matter (NOM) at the surface of the manganese oxide. Interestingly, the mechanism behind NOM adsorption onto manganese oxides remains unclear. Therefore, in this study, the adsorption kinetics and equilibrium of different NOM isolates to synthetic manganese oxide (birnessite) and natural manganese oxide (Mn sand) were investigated. Natural manganese oxide is composed of both amorphous and well-crystallised Mn phases (i.e., lithiophorite, birnessite, and cryptomelane). NOM adsorption on both manganese oxides increased with decreasing pH (from pH. 7 to 5), in agreement with surface complexation and ligand exchange mechanisms. The presence of calcium enhanced the rate of NOM adsorption by decreasing the electrostatic repulsion between NOM and Mn sand. Also, the adsorption was limited by the diffusion of NOM macromolecules through the Mn sand pores. At equilibrium, a preferential adsorption of high molecular weight molecules enriched in aromatic moieties was observed for both the synthetic and natural manganese oxide. Hydrophobic interactions may explain the adsorption of organic matter on manganese oxides. The formation of low molecular weight UV absorbing molecules was detected with the synthetic birnessite, suggesting oxidation and reduction processes occurring during NOM adsorption. This study provides a deep insight for both environmental and engineered systems to better understand the impact of NOM adsorption on the biogeochemical cycle of manganese.